(untitled) (REGE Revista de Gestão, 2007)
Capital structure and financial performance of Brazilian, Argentinean and Chilean companies were compared to identify differences using a multiple cross section study made of 1996 to 2005. Samples were taken from the Economatica® for examination of the variables of debt over PL (ENDV), operational profitability over total assets (ROAOP) and profitability over PL (ROE). Variance analysis was used to detect significant differences between companies in these countries and the Scheffé test identified countries differing from the averages. Significant differences were found in average ENDV and ROAOP in five of the ten years and in ROE for seven years of these ten years. Brazilian companies, in general, differed from the Chilean and Argentinean ones; however, no significant differences were noted between the Argentinean and Chilean companies. Descriptive analysis showed that Brazilian companies had a higher ENDV for all the years, lower ROAOP during the first four years and a lower ROE for the period studied.